ENGLISH TEACHERS’ PERCEPTIONS OF LANGUAGE ASSESSMENT LITERACY AT JUNIOR HIGH SCHOOLS OF KERINCI - Nezfi, Nauval Zalmi (TELL - US JOURNAL, 2024)
Based on the observation in the field, the researcher identify the problem as follow: English teachers look at assessment as something that is final with a purposeof just giving students a grade. The purpose of this research was to To find out how do English teachers’ perception of Language Assessment Literacy  at SMP Kerinci. The design of this research was quantitatif descriptive. In collecting the data, the researcher was distributed questionnaire to the respondents to assess their perception on LAL. Based on the finding of the resrech, 1). the total mean of teachers’ perception of Language Assessment Literacy (LAL)  was 3.37. It mens that the teachers’ perception of LAL was at medium level. 2). the item anlysis of Langauge assessment literacy of  knowledge components it was found that the total mean of this components was 2.63. It means that the teacher sometimes used knowledge components in LAL. 3). Then, the item anlysis of Langauge assessment literacy of  skills components it was found that the total mean of this components was 2.83. It means that the teacher sometimes used skills components in LAL. 4). In other hand, the item anlysis of Langauge assessment literacy of  principles  components it was found that the total mean of this components was 3.56. Thus, it can be concluded that the teachers’ perception of  LAL of principles component was at High level criteria. It means that the teacher usualy/often used principles  components in LAL